Analisis Nilai Karakter dalam Dongeng Pada Buku Siswa Tema 8 Daerah Tempat Tinggalku Kelas IV Sekolah Dasar - Satriyo Agung Budi Harjono; Ikha Listyarini; Mei Asri Untari (STKIP Andi Matappa Pangkep, 2022)
The value of character in learning is a must. This study analyzes the value of characters in students' books. This study uses a qualitative approach, the data analysis technique is qualitative descriptive of a literary work by looking for the character values contained therein. The data in this study were obtained through observation, interviews, documentation, listening and notes. The results of the study showed that the book